The Role of Carbon Market in Net Zero Emission: Economic Impact of Carbon Credit and Forest Conservation in Indonesia - Ayuni Septiani Saputri; Diswandi Diswandi (Journal of Enterprise and Development (JED), 2025)
Purpose: This study analyzes the role of the carbon market in achieving Net Zero Emissions, focusing on how carbon credit development and tropical forest conservation can create new economic opportunities in Indonesia.Method: This research employs a qualitative descriptive approach, using a case study of the REDD+ project in Indonesia. Data was collected through semi-structured interviews with various stakeholders, including government officials, local communities, and environmental organizations. Thematic analysis was utilized to identify key patterns related to the economic benefits and technical challenges of the carbon market.Result: The study finds that the carbon market can provide substantial economic benefits through carbon credit trading, attracting investments in green technology and sustainability programs. It also has the potential to raise awareness of the importance of conserving tropical forests as critical carbon sinks. However, challenges such as regulatory gaps, limited community participation in decision-making, and technological constraints for monitoring and reporting must be addressed.Practical Implications for Economic Growth and Development: Indonesia can harness the carbon market to drive sustainable economic growth while supporting environmental preservation and global carbon emission reductions. Active stakeholder engagement, technological capacity building, and regulatory strengthening are crucial for the successful implementation of the carbon market in the future.